Paper-Based Optical Sensor for Detection of Bacteria - V. A. Hovhannisyan; G. G. Poghosyan; V. K. Gasparyan (International Journal of Biomedicine)
A paper-based visual optical sensor for detecting bacteria was developed. The principle of the assay is to use lentil lectin immobilized on paper as a bacteria-binding primary ligand and the same lectin conjugated with gold nanoparticles as a detecting ligand. This approach permits the detection of gram-positive bacteria with an absorbance at 600 nm of 0.3, whereas for gram-negative bacteria of 0.4.